Pengaruh Brand Ambassador dan E-Wom terhadap Brand Image Pelembab Pond’s: - Leilani, Elvina Rosa; Kusnanto, Danang (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
This study aims to investigate the impact of brand ambassadors and electronic word-of-mouth (E-WOM) on the brand image of Pond's moisturiser products. A descriptive and verification approach method was used in this study, which was combined with a quantitative approach. The questionnaire was directed to 347 respondents who are followers of the @pondsindonesia Instagram account. The results of the analysis show that the use of Brand Ambassadors and E-WOM has a positive impact on Pond's Brand Image. Furthermore, it was found that Brand Ambassadors have a more dominant influence in shaping consumers' positive perceptions of the brand. This research provides a deeper understanding of how the influence of marketing elements such as Brand Ambassadors and E-WOM can affect brand image on social media platforms. Keywords: Brand Ambassador; E-Wom; Brand Image